Activity of nacubactam (RG6080/OP0595) combinations against MBL-producing Enterobacteriaceae. (24th December 2018) - Mushtaq, Shazad; Vickers, Anna; Woodford, Neil; Haldimann, Andreas; Livermore, David M
Abstract: Background: Diazabicyclooctanes (DBOs) are promising β-lactamase inhibitors. Some, including nacubactam (OP0595/RG6080), also bind PBP2 and have an enhancer effect, allowing activity against Enterobacteriaceae with MBLs, which DBOs do not inhibit. We tested the activity of nacubactam/β-lactam combinations against MBL-producing Enterobacteriaceae. Methods: Test panels comprised (i) 210 consecutive Enterobacteriaceae with NDM or VIM MBLs, as referred by UK diagnostic laboratories, and (ii) 99 supplementary MBL-producing Enterobacteriaceae, representing less prevalent phenotypes, species and enzymes. MICs were determined by CLSI agar dilution. Results: MICs of nacubactam alone were bimodal, clustering at 1–8 mg/L or >32 mg/L; >85% of values for Escherichia coli and Enterobacter spp. fell into the low MIC cluster, whereas Proteeae were universally resistant and the Klebsiella spp. were divided between the two groups. Depending on the prospective breakpoint (4 + 4 or 8 + 4 mg/L), and on whether all isolates were considered or solely the Consecutive Collection, meropenem/nacubactam and cefepime/nacubactam inhibited 80.3%–93.3% of MBL producers, with substantial gains over nacubactam alone. Against the most resistant isolates (comprising 57 organisms with MICs of nacubactam >32 mg/L, cefepime ≥128 mg/L and meropenem ≥128 mg/L), cefepime/nacubactam at 8 + 4 mg/L inhibited 63.2% and meropenem/nacubactam at 8 + 4 mg/L inhibited 43.9%. Aztreonam/nacubactam, incorporating an MBL-stable β-lactam partner, was almost universally active against the MBL producers and, unlike aztreonam/avibactam, had an enhancer effect. Conclusions: Nacubactam combinations, including those using MBL-labile β-lactams, e.g. meropenem and cefepime, can overcome most MBL-mediated resistance. This behaviour reflects nacubactam's direct antibacterial and enhancer activity.